Effects of an altered suckling method on piglet performance during late lactation and the nursery period - Gourley, K. M.; Frobose, H. L.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S.; Goodband, Robert D.; Nelssen, Jim L.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
The effects of an altered suckling method (ALT) on nursery pig performance were studied in a 14-d experiment encompassing late lactation and the early nursery period. A total of 611 pigs (PIC 327 × 1050) nursing 54 sows were used in 2 farrowing groups. Sows were allotted to treatments on d 18 of lactation when all but the 5 lightest-weight pigs from each ALT litter were split-weaned (SW) and moved to the nursery. The lightweight pigs in the ALT litters were paired within parity group such that two litters were combined. These combined litters rotationally suckled (RS) each sow of the pair for 12 h/d from d 18 until weaning on d 25. Pigs in control litters were weaned on d 21. At weaning, pigs were randomly assigned to pens (7 pigs/pen). All weaned pigs received a common feed budget of 4 lb of Phase 1 followed by a Phase 2 diet. Pigs were weighed on d 18, 21, 25, 28, and 32 of age. Differences in weight gain, variation in growth within litter, and the association between piglet weight category on d 18 and treatment effects were evaluated. An interaction was detected (P < 0.01) for pig weights and weight gain from d 18 to 32 because the RS pigs gained 15% more than lightweight controls, whereas SW pigs were 15% lighter than heavyweight controls on d 32. Overall variation as measured by the changes in CV and SD was 50% less (P < 0.01) within ALT litters compared with controls. When pig weight groups were compared, the ALT treatment benefited (P < 0.001) growth of light (<10 lb) pigs but decreased (P < 0.01) the weight gain of heavy (>14 lb) pigs. Overall, performance was similar between ALT and control pigs, but the apparent improvement in weight variation observed within ALT litters warrants additional investigation.
Keywords: Swine; Intermittent suckling; Litter variation; Nursery pig; Split weaning